INTEGRATION OF SCIENCE IN THE PERSPECTIVE OF ISLAMIC EDUCATIONAL PHILOSOPHY AND ITS IMPLICATIONS IN REALIZING HOLISTIC EDUCATION - Desfita, Vivi; Salminawati, Salminawati; Usiono, Usiono (Asosiasi Dosen Perguruan Tinggi Islam, 2024)
This study examines the concept of integration of knowledge in the context of Islamic education, focusing on the perspective of Islamic educational philosophy. The main objective of this study is to understand the meaning and relevance of integrating knowledge within the framework of Islamic thought to realize holistic education. This study uses a literature analysis method, exploring the theoretical and practical understanding of integrating knowledge from related primary and secondary sources. The results of this study indicate that integration of knowledge according to the perspective of Islamic educational philosophy is not only about combining curricula but also involves a holistic learning experience that combines spiritual, intellectual, and practical aspects. A deep understanding of Islamic values is integrated into the educational process to form individuals who are not only academically competent but also have good morals and strong spiritual awareness. This study contributes to the literature on Islamic education by providing a deeper understanding of the concept of integration of knowledge and a basis for developing educational strategies that focus on holism and harmony between knowledge and spiritual values in the context of Islamic education.